The Influence of Lactic Acid Bacteria Fermentation on the Bioactivity of Crayfish (Faxonius limosus) Meat - Natalia Śmietana; Przemysław Śmietana; Emilia Drozłowska; Łukasz Łopusiewicz (Fermentation, 2023)
In recent years, new raw materials have been sought for use in processing. This category certainly includes invasive crayfish Faxonius limosus. One of the problems associated with their use is their short microbiological shelf life. Therefore, in the research presented here, an attempt was made to ferment crayfish meat with strains of Lactiplantibacillus plantarum, Lacticaseibacillus rhamnosus, Lactobacillus casei, and yogurt culture. The analyses included an evaluation of changes in the microbial quality of the material, the content of free amino acids, reducing sugars, ascorbic acid, and the antioxidant properties of the fermented meat. Changes in the canthaxanthin content and the number of sulfhydryl groups and disulfide bridges were also evaluated. The study showed that carrying out lactic fermentation resulted in a decrease in meat pH (8.00 to 7.35–6.94, depending on the starter culture). Moreover, the meat was characterized by an increase in FRAP (2.99 to 3.60–4.06 mg AAE/g), ABTS (2.15 to 2.85–3.50 μmol Trolox/g), and reducing power (5.53 to 6.28–14.25 μmol Trolox/g). In addition, the study showed a favorable effect of fermentation on the content of sulfhydryl groups in the meat as well as for ascorbic acid content. The results obtained can serve as a starting point for the further development of fermented products based on crayfish meat.